KEPATUHAN BANK SYARIAH TERHADAP FATWA DEWAN SYARIAH NASIONAL PASCA TRANSFORMASI KE DALAM HUKUM POSITIF - Agus Waluyo (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The purpose of this research is to analize the Islamic Bank Commitment to implementation of fatwa Sharia National Board that has been transformed into positive law. The design of this study is qualitative approach. This field research using qualitative approach with data from interviews with the banks. The result shows that the fatwa related to Islamic banks that has been transformed into positive law can be used as a legal basis to be obeyed. The results showed that the Islamic Bank commitment to implementation of fatwa Sharia National Board has not been effective and efficient. The functions of sharia by the director of compliance to all employees of Islamic bank normatively has been implemented in accordance with the principles of compliance, the compliance culture, management risk, and the values. The role of Sharia Supervisory Board in sharia compliance monitoring system has been implemented but not optimal.